Overview of Midwives’ Performance in Providing Antenatal Care (ANC) Services at Cipedes Public Health Center, Bandung Regency - Bonita, Nely; Darsono, Filla Alfazriani (Rifa'Institute, 2025)
Introduction: The performance of midwives in providing Antenatal Care (ANC) services plays a critical role in improving maternal and neonatal health. ANC services must be delivered according to established standards to ensure quality outcomes. Objective: This study aimed to assess the performance of midwives in ANC services at Health Centres across Bandung Regency, focusing on five key components: service quality, communication, capability, speed, and initiative. Method: This study employed a descriptive quantitative research design. The research was conducted in Health Centres across Bandung Regency, with a total sample of 30 midwives selected using total sampling. Data were analyzed descriptively to determine performance levels across the components. Results and Discussion: The findings showed that most midwives demonstrated good performance. Specifically, 90% showed good performance in the service quality component, 66.7% in communication, 53.3% in capability, 63.3% in speed, and 53.3% in initiative. These results indicate that while the overall performance is satisfactory, improvements are still needed in several areas, particularly in capability and initiative. Conclusion: The performance of midwives in ANC services across Bandung Regency is generally good. However, enhancing ANC classes for pregnant women and utilizing online platforms for maternal health monitoring are recommended to further improve service delivery and maternal outcomes.